PENGARUH MODEL PROBLEM BASSED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI - Weni, Tika Candra; Ratna, Ellya; Hafrison, Mohammad (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ The purpose of this research there are three. First, Describe the influence of the skill of writing text about a grade X SMA Semen Padang before using the models of Problem Based Learning assisted audiovisual media. Second, it describes the influence of writing skills Text about a grade X SMA Semen Padang after using the model of Problem Based Learning assisted audiovisual media. Third, describe the influence of the application of the model of Problem Based Learning assisted media audiovisual against the writing skills text about a grade X SMA Semen Padang. This type of research is quasi experiment method with quantitative. Based on the data analysis, the use of a model of Problem Based Learning assisted audiovisual media influence on writing skills text about a grade X SMA Semen Padang.Â Kata kunci: pengaruh, Problem Bassed Learning, audiovisual, teks biografi